Refugees in Canada and Germany: from research to policies and practice - Korntheuer, Annette (Schriftenreihe, 2020)
This edited collection offers an in-depth look at the reactions of Germany and Canada - two countries that have responded to the 21st century ‘age of displacement’ in very different ways - and the creative solutions and often collaborative efforts these host societies have undertaken to support the sudden arrival of newcomers within their nation’s borders. The migration of significantly high numbers of asylum seekers and refugees between 2015 and 2018 presented destination and resettlement societies both a sizable challenge and an opportunity to respond effectively to the imminent needs of this cohort. Germany and Canada emerged as leaders on the global stage for how they responded and the innovative ways they were able to bring together different social actors and stakeholders locally, nationally and globally. This volume is the result of an ongoing international, collaborative effort to monitor and evaluate these responses - from research to policies and practice. The objective is to mobilize knowledge produced through the latest research on key issues relating to the resettlement and integration of refugees in Germany and Canada in a timely and accessible manner. The works presented here not only show evidence based results on resettlement and integration in Canada and Germany, they also provide valuable insights that can support government agencies, service providers and members of civic society to rapidly respond to factors that threaten the wellbeing of refugees and will be instrumental to the successful integration of future cohorts.Dieses Sammelwerk beschreibt die Reaktionen Deutschlands und Kanadas auf das 'age of displacement' des 21. Jahrhunderts. Es zeigt Lösungsansätze und gemeinsame Anstrengungen auf, die unternommen wurden, um die seit 2015 Neuzugewanderten zu unterstützen. Zudem werden kritische, gesellschaftliche und politische Antworten auf Fluchtzuwanderung analysiert. Die Zuwanderung einer hohen Anzahl von Asylsuchenden und Geflüchteten zwischen 2015 und 2018 stellte Deutschland und Kanada zwar vor große Herausforderungen, eröffnete jedoch auch die Chance, effektiv mit den Erwartungen unterschiedlicher Interessengruppen umzugehen. Beide Länder zeigen sich als wichtige Akteure, die sich bemühen, diese auf lokaler, nationaler und globaler Ebene zu vernetzen, um geeignete und innovative Antworten auf drängende gesellschaftliche Fragen zu finden. Dieser Band ist das Ergebnis einer internationalen Zusammenarbeit, um diese Antworten und Reaktionen - from research to policies and practice - zu analysieren und zu evaluieren. Ziel ist es, neue Forschungsergebnisse zu Schlüsselthemen im Zusammenhang mit Fluchtmigration und Integration in Deutschland und Kanada zugänglich und nutzbar zu machen. Die hier vorgestellten Beiträge diskutieren nicht nur evidenzbasierte Ergebnisse zur Integration von Asylsuchenden und Geflüchteten in Kanada und Deutschland, sondern sie liefern auch wertvolle Ansätze, um öffentliche Akteure, soziale Institutionen und Mitglieder der Zivilgesellschaft dabei zu unterstützen, das Wohlbefinden und die Integration von Neuzugewanderten zu sichern.
Gesehen am 26.10.2020